PENGEMBANGAN OBJEK WISATA KAMBANG IWAK PARK SEBAGAI PARU-PARU KOTA PALEMBANG - Nyayu Ully Auliana; Dwi Hanadya; M Bambang Purwanto (Nawasena: Jurnal Ilmiah Pariwisata, 2022)
This descriptive qualitative research was done in order to find out the development strategy for Kambang Iwak Park, a tourism site at Palembang city. It has been found that maintenance of public facilities around the park is not managed properly, trees that are brittle and prone to fall, moreover, the villagers have no awareness to the value of their environmental tourism. These facts are the main reason why researchers conducted this research. Data obtained by using observations, interviews, and documentation carried out in the Kambang Iwak Park. Data analysis using SWOT analysis (Strengths, Weaknes, Opportunities and Threat). The results showed that the Kambang Iwak tourism park needed to: 1. A Counseling to increase and raise awareness of villagers about the importance awareness of tourist sites, 2. providing counseling and teaching to the public so that they are aware of environmental cleanliness, 3. developing tourism attractions, 4. repairing and providing tourist attraction facilities and infrastructure, 5. to build a parking lot, 6. to create an environmentally friendly area.